Perinatology: The novel branch of canine theriogenology - Sánchez Riquelme, Alfonso (2021)
Perinatology is understood as the scientific discipline, a branch of obstetrics and pediatrics, which deals with promoting the health of the mother, foetus and new-born during the perinatal period, as well as the clinical study, diagnosis, treatment and research of their diseases. In the canine species (Canis lupus familiaris) the perinatal period is defined as the phase from the last stage of intrauterine foetal development to the end of the neonatal period. There are significant losses in the perinatal period due to mortality, which has led to important advances in knowledge about gestation, delivery, assessment of foetal maturity, prognosis of delivery, caesarean section planning and new-born assessment. In this context, perinatology is an area of canine medicine which is experiencing increasing demand. From a professional perspective, this is challenging in terms of promoting science-based breeding. Therefore, the purpose of this literature review was to review and discuss topics of this novel discipline to contribute to its better understanding.